Narratives, path dependence and case studies - Araujo, Luis (Revista Economia & Gestão, 2008)
The purpose of this article is to reflect on the use of narratives in case studies. The main argument developed here is that constructing narratives embodies important theoretical assumptions about the nature of theworld and temporal processes. A secondary argument concerns the difference between lay and academic narratives. Although social scientists have little choice but work with linear narratives and standard stories as primary empirical material, theoretically informed narratives should striveto construct more subtle and nuanced narratives about the social world.